Dealer balance sheets and bond liquidity provision - Tobias Adrian; Nina Boyarchenko; Or Shachar (Federal Reserve Bank of New York, 2016)
Do regulations decrease dealer incentives to intermediate trades? Using a unique data set of dealer-bond-level transactions, we construct the dealer-specific market liquidity metrics for the U. S. corporate bond market. Unlike prior studies, the transactions that we observe are uncapped in size and include the identity of dealer counterparties to the transaction. The granular nature of our data allows us to link changes in liquidity of individual corporate bonds to dealer transaction activity. We show that, in the full sample, bond-level liquidity is higher when institutions that are active traders in the bond are more levered, have higher trading revenue, have higher liquidity mismatch, are more vulnerable, have lower risk-weighted assets, are less reliant on repo funding, and hold fewer illiquid assets. In the rule implementation period (post January 2014), bonds traded by more vulnerable institutions and institutions with greater liquidity mismatch are less liquid, suggesting that prudential regulations may be having an effect on bond market liquidity.
Keywords: G12; G18; G21; 330; bond liquidity; regulation; dealer constraints